Characterization of the MYB Genes Reveals Insights Into Their Evolutionary Conservation, Structural Diversity, and Functional Roles in Magnaporthe oryzae - Lee, Sehee; Völz, Ronny; Song, Hyeunjeong; Harris, William; Lee, Yong-Hwan (Frontiers in Microbiology, 2021)
The myeloblastosis (MYB) transcription factor family is evolutionarily conserved among plants, animals, and fungi, and contributes to their growth and development. We identified and analyzed 10 putative MYB genes in Magnaporthe oryzae (MoMYB) and determined their phylogenetic relationships, revealing high divergence and variability. Although MYB domains are generally defined by three tandem repeats, MoMYBs contain one or two weakly conserved repeats embedded in extensive disordered regions. We characterized the secondary domain organization, disordered segments, and functional contributions of each MoMYB. During infection, MoMYBs are distinctively expressed and can be subdivided into two clades of being either up- or down-regulated. Among these, MoMYB1 and MoMYB8 are up-regulated during infection and vegetative growth, respectively. We found MoMYB1 localized predominantly to the cytosol during the formation of infection structures. ΔMomyb1 exhibited reduced virulence on intact rice leaves corresponding to the diminished ability to form hypha-driven appressorium (HDA). We discovered that MoMYB1 regulates HDA formation on hard, hydrophobic surfaces, whereas host surfaces partially restored HDA formation in ΔMomyb1. Lipid droplet accumulation in hyphal tips and expression of HDA-associated genes were strongly perturbed in ΔMomyb1 indicating genetic interaction of MoMYB1 with downstream components critical to HDA formation. We also found that MoMYB8 is necessary for fungal growth, dark-induced melanization of hyphae, and involved in higher abiotic stress tolerance. Taken together, we revealed a multifaceted picture of the MoMYB family, wherein a low degree of conservation has led to the development of distinct structures and functions, ranging from fungal growth to virulence.